Renal manifestation of Birt–Hogg–Dubé syndrome depicted by 18F-fludeoxyglucose positron emission tomography/computed tomography in a patient with hurtle cell thyroid malignancy - Emmanouil Panagiotidis; Nagabhushan Seshadri; Sobhan Vinjamuri (World Journal of Nuclear Medicine)
Birt–Hogg–Dubé (BHD) syndrome is an autosomal dominant genetic disorder characterized by small papular skin lesions (fibrofolliculomas) causing susceptibility to kidney cancer, renal and pulmonary cysts, spontaneous pneumothoraces, and several noncutaneous tumors. We report a case of a 67-year-old woman, with a previous history of right hemithyroidectomy for adenomatous lesion. She presented with a swelling in the right thyroid bed that on subsequent biopsy revealed features of metastatic carcinoma. 18F-fludeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) performed for the detection of primary malignancy showed increased high-grade metabolic activity in the right supraclavicular soft tissue mass extending into the superior mediastinum. Moreover, on low-dose CT, there have been bilateral renal interpolar cortical lesions with mild metabolic activity. Given the fact that the right neck mass was highly unlikely to represent renal metastases in the absence of widespread metastatic disease, surgical excision of the right neck mass was performed. The histology of the mass was in keeping with hurtle cell thyroid carcinoma. In regard to renal lesions, bilateral partial nephrectomy was performed, which was consistent with chromophobe renal cell carcinoma, raising the suspicion of BHD that was confirmed by the subsequent genetic evaluation. It is well established that 18F-FDG PET/CT study is not an optimal modality for evaluation of renal lesions. However, careful assessment of the CT features in conjunction with the associated metabolic activity of the 18F-FDG PET component increases the diagnostic accuracy of PET/CT.